Managing Higher Education Institutions - Shrestha, Dil Prasad (Administration and Management Review, 2010)
This paper briefly describes the importance of the application of management functions to improve educational outcomes. It tries to highlight changes in management paradigm and traces a brief history of the rise of strategic management. Changes in management paradigm and the rise of strategic management have helped education managers improve their organizational performance. The paper also identifies some serious challenges facing education managers in order to achieve educational goals. Finally, the environmental context of managing higher education institutions and its implications to education managers are also briefly discussed. Administration and Management Review Volume 21, No. 2, 2009 Page: 22-39